Size segregated ionic species collected in a harbour area. (May 2022) - Navarro-Selma, B.; Clemente, A.; Nicolás, J.F.; Crespo, J.; Carratalá, A.; Lucarelli, F.; Giardi, F.; Galindo, N.; Yubero, E.
Abstract: Water-soluble ions were analysed in size segregated aerosol samples collected in the port of Alicante (Southeastern Spain) during summer and winter using a multistage cascade impactor. Seasonal variations in the size distributions of the analysed components and the influence of bulk materials handling (loading/unloading and stockpiling) at the docks were investigated. The size distributions of SO4 2−, NH4 + and K + were characterized by prominent peaks in the condensation and droplet modes, both in summer and winter, while those of Ca 2+, Na +, Mg 2+ and Cl − had a main peak centred at ∼4 μm. Although oxalate size distributions were similar during both seasons, the fraction of coarse-mode oxalate increased in summer most likely as a result of volatilization and repartition processes or reactions of oxalic acid with coarse alkaline particles. Nitrate size distributions were dominated by a coarse mode; however, during winter, modal peaks in the submicron size range were also observed due to favourable conditions for the formation of fine-mode NH4 NO3 . Harbour activities had a significant impact only on the concentrations of calcium, particularly in the coarse fraction, during both summer and winter. Graphical abstract: Image 1 Highlights: Aerosol size distributions in a port environment has been studied. The possible origin of particle size distributions of inorganic ions is explained. The impact of port activities on aerosol size distributions is analysed. Seasonal changes of aerosol size distributions are evaluated.